HUBUNGAN TINGKAT PENGETAHUAN DENGAN MANAJEMEN DIRI PASIEN DIABETES MELITUS TIPE 2 DI POLI RAWAT JALAN SATU RS SWASTA PALANGKA RAYA - Apir; Titin, Rolina (Poltekkes Kemenkes Yogyakarta, 2025)
Self-management in people with diabetes mellitus is an action that aims to protect the patient against the disease and as an effort to prevent complications. Individuals who have good self-management are able to increase their independence in managing their disease independently. In addition to self- management, people with diabetes mellitus also need to have good knowledge. To determine the relationship between knowledge level and self-management of type 2 diabetes mellitus patients in the outpatient polyclinic of a private hospital in Palangka Raya. Using the correlation method using accidental sampling technique. The sample in this study amounted to 50 people. The instruments used in this study were a knowledge level questionnaire about diabetes mellitus (DKQ 24) and a diabetes mellitus self- management questionnaire (DSMQ) which were closed because they already had 40 answer choices and were distributed to respondents in February-March 2023. The results of this study indicate that there is a relationship between the level of knowledge and the self-management of patients with type 2 diabetes mellitus in the single outpatient polyclinic of the Palangka Raya private hospital, with a p value = 0.05 with a sperm rank test correlation of 0.006. There is a relationship between the level of knowledge and self-management of type 2 diabetes mellitus patients in the outpatient polyclinic of a private hospital in Palangka Raya.